Exhaust system optimization using GT- Power - Mohiuddin, A. K. M. (IIUM Press, 2011)
The exhaust system consists of the exhaust manifold, the header, the catalytic converter, the muffler, and the tailpipe. Certain flow characteristics must be met for the optimal performance of the exhaust system. The main objective of this chapter is to design exhaust system (particularly the exhaust manifold) using GT-Power software and to optimize its performance.